THE SENSE OF JUSTICE AND ITS MORAL SIGNIFICANCE IN MAWLANA JALAL AL-DIN MUHAMMAD RUMI’S THOUGHT - Ilgaroglu, Muhammet Caner; Arman, Arief (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2025)
This article analyses the moral significance of the sense of justice in the thought of Mawlana Jalal al-Din Rumi (d. 1273). Through a systematic close reading and hermeneutical analysis of Rumi’s principal works, Mathnawī and Fīhi Mā Fīh, it explores the individual, social, and metaphysical dimensions of justice within his moral philosophy. Rumi does not perceive justice merely as a legal or social principle but as a divine moral faculty inherent in human nature. The findings reveal that the sense of justice plays a pivotal role in grasping moral principles, cultivating ethical character, maintaining social harmony, and achieving spiritual proximity to the Divine. Employing metaphors such as the “scale” (mīzān) and the “mirror of the heart (gönül),” Rumi suggests that purifying the soul (nafs) from desires and passions activates this innate moral sense. Ultimately, Rumi presents justice as a divine mechanism that reflects moral balance, wisdom, and virtuous action. By highlighting the sense of justice as an internalized metaphysical virtue that transcends legal norms, this study offers a novel contribution to contemporary Islamic moral philosophy.